Interleukin-6 receptor blockade induces limited repair of bone erosions in rheumatoid arthritis: A micro CT study - Finzel, Stephanie; Rech, Jürgen; Schmidt, Sarah; Engelke, Klaus; Englbrecht, Matthias; Schett, Georg (Annals of the Rheumatic Diseases, 2013)
Introduction: Interleukin-6 receptor (IL-6R) blockade improves the signs and symptoms of rheumatoid arthritis (RA) and retards bone damage. Whether IL-6R blockade allows repair of existing bone erosions is so far unclear. Methods: This study examined bone erosions in the metacarpophalangeal joints of 20 patients receiving treatment with the IL-6R blocker tocilizumab using micro CT (μCT). The maximal width and depth of individual bone erosions was measured at baseline and after 1 year of treatment. Results: 133 bone erosions were identified at baseline with a mean (±SD) size of 2.23±1.26 mm and depth of 2.16±1.50 mm. Distribution analysis showed predominant involvement of the second compared with the third and fourth metacarpophalangeal joints, the metacarpal heads compared with the phalangeal bases and the radial quadrants compared with all other surfaces. Repair of bone erosions during tocilizumab treatment was confined to those lesions showing sclerosis at baseline and/or at follow-up and those with a width larger than 1.6 mm. The mean decrease in width of sclerosed erosions was thus 0.14±0.05 mm (p=0.0086) and 0.20±0.08 mm (p=0.019) for sclerosing lesions after 1 year of treatment. Conclusions: Blockade of IL-6R by tocilizumab can induce limited repair in a subset of erosions, particularly in large lesions with sclerosis. Repair of erosions during tocilizumab treatment reflects the favourable impact of IL-6R blockade on local bone remodelling in patients with RA.
CRIS-Team Scopus Importer:2021-02-03